The Concept for the Development of Higher Education Institutions in the Field of Architecture (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2026)
This article examines contemporary challenges and development pathways for higher education institutions in the field of architecture, with a focus on aligning national educational systems with international standards and labor-market demands. The introduction outlines the rapid transformation of the architectural profession under the pressures of urbanization, climate change, digitalization, and growing social responsibility. Despite ongoing reforms, a significant knowledge gap persists in integrating practice-oriented learning, digital technologies, and sustainable development principles into architectural curricula, particularly in the context of developing countries such as Uzbekistan.The study employs a qualitative analytical method based on a review of national policy documents, international normative frameworks, and recent scientific literature on architectural education. Comparative analysis is used to identify mismatches between existing educational models and emerging professional requirements.The findings indicate that current architectural programs are often overly theoretical, weakly connected to industry, and insufficiently responsive to digital and interdisciplinary shifts. International experience highlights the effectiveness of competency-based curricula, transdisciplinary design studios, “living laboratories,” and hybrid learning formats in bridging this gap.The results demonstrate that adopting modular, project-oriented, and digitally supported educational models can significantly enhance graduate competitiveness and professional readiness. The article concludes that systematic integration of international standards, industry partnerships, and sustainable development principles is essential for reforming architectural education.The implications of this study are relevant for policymakers, university administrators, and educators seeking to modernize architectural education systems and prepare architects capable of addressing complex socio-environmental challenges of the 21st century.